Unprepared and unprotected: Graduating medical students’ knowledge, attitudes, and practices regarding drug-resistant tuberculosis in Cape Town, South Africa - Harrison, Michael J.; Watts, Jonathan; Rosslee, Michael-Jon; von Delft, Arne; van der Westhuizen, Helene-Mari (International Journal of Infection Control, 2021)
South Africa has a high burden of drug-resistant tuberculosis (DR-TB), which has a particularly high mortality among healthcare workers. Junior clinicians deliver key DR-TB services and require training in DR-TB management and prevention. This study aimed to investigate graduating medical students’ knowledge, attitudes, and practices relating to DR-TB, including management, infection control measures, and occupational health services. This cross-sectional, questionnaire-based study at the University of Cape Town, South Africa, recruited final year medical students and included 87 participants. The mean DR-TB knowledge score was 4.7 points (95% confidence interval [CI]: 4.42–5.06, maximum score 8 points). Students reported challenges in accessing respiratory protection, with half (47.7%) struggling to find an N95 respirator when needed. DR-TB exposure was reportedly common. Three students reported prior TB disease, approximately half (n = 49, 55.9%) reported personal concern of active DR-TB disease during undergraduate studies, and the majority (n = 80, 91.9%) correctly perceived themselves to be at increased risk compared to the general population. Medical students are currently unprepared for their role in managing DR-TB in South Africa and unprotected against occupational illness during their studies. This should be addressed in undergraduate curricula and in establishing comprehensive occupational health policies. Resilient personal protective equipment (PPE) supply chains, infection control training, and comprehensive occupational health support have relevance to both DR-TB and novel pathogens, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).